Diamond Surfaces with Air‐Stable Negative Electron Affinity and Giant Electron Yield Enhancement. (3rd June 2013) - O'Donnell, Kane M.; Edmonds, Mark T.; Ristein, Juergen; Tadich, Anton; Thomsen, Lars; Wu, Qi‐Hui; Pakes, Chris I.; Ley, Lothar
Abstract The presence of an air‐stable negative electron affinity (NEA) on lithium‐covered oxygen‐terminated diamond after a thermal activation process is demonstrated. The NEA is unequivocally established by the onset of photoelectron yield at the bandgap energy of 5.5 eV. This surface exhibits a secondary electron yield enhancement by a factor of 200, compared to a surface with positive electron affinity. The surface chemistry leading to the necessary surface dipole was elucidated by core‐level photoemission spectroscopy in conjunction with previous theoretical calculations. The insensitivity to the details of the deposition process opens a route to practical and robust negative‐electron affinity devices based on diamond.